2016
DOI: 10.3171/2015.6.jns1565
|View full text |Cite
|
Sign up to set email alerts
|

The safety of Pipeline flow diversion in fusiform vertebrobasilar aneurysms: a consecutive case series with longer-term follow-up from a single US center

Abstract: OBJECT Pessimism exists regarding flow diversion for posterior circulation aneurysms because of reports of perforator territory infarcts and delayed ruptures. The authors report the results of patients who underwent Pipeline Embolization Device (PED) flow diversion using novel strategies for treatment of fusiform posterior circulation aneurysms, and compare these results with those from previously reported series. METHODS The authors conducted a retrospective review of data from consecutive patients with fusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(64 citation statements)
references
References 19 publications
4
59
1
Order By: Relevance
“…In a study of seven patients undergoing flow diversion for treatment of non-saccular posterior circulation aneurysms, Siddiqui et al demonstrated remarkably high mortality (57%) and thromboembolic complications (72%) with correspondingly low rates of favorable neurologic outcomes (29%). 22 17 However, in a subsequent study performed at the same institution, Natarajan et al used more refined selection criteria—namely, the avoidance of holobasilar aneurysms, or aneurysms with a large amount of thrombus—and reported 0% mortality, 8% thromboembolic complication rate, and 92% good neurologic outcomes 9. Indeed, in the present study, the rate of good neurologic outcome in the holobasilar aneurysm group (2/11, 13%) was lower than other locations (33–83%).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of seven patients undergoing flow diversion for treatment of non-saccular posterior circulation aneurysms, Siddiqui et al demonstrated remarkably high mortality (57%) and thromboembolic complications (72%) with correspondingly low rates of favorable neurologic outcomes (29%). 22 17 However, in a subsequent study performed at the same institution, Natarajan et al used more refined selection criteria—namely, the avoidance of holobasilar aneurysms, or aneurysms with a large amount of thrombus—and reported 0% mortality, 8% thromboembolic complication rate, and 92% good neurologic outcomes 9. Indeed, in the present study, the rate of good neurologic outcome in the holobasilar aneurysm group (2/11, 13%) was lower than other locations (33–83%).…”
Section: Discussionmentioning
confidence: 99%
“…27 Eleven (90%) of 12 patients recovered to a modified Rankin Scale score of 0 or 1 after a clinical follow-up duration of 22 months, with only 1 patient experiencing a perforator territory infarction with poor clinical outcome (modified Rankin Scale Score 4). At last follow-up, the complete occlusion rate was 100%, and the PEDs were patent.…”
mentioning
confidence: 95%
“…This deployment modality has an additional benefit to lower post procedural ischemia of brain stem, which was quietly frequently noted both in single-layer or multi-layers' flow-diverted cases [10]. Applying this technique, only one PED was used and the perforators were directly covered by the high-porous stent instead of a PED, so the post procedure ischemia rate might be of minimal concern; this might be the account for why our patient recovered from the procedure without any neurologic deficits.…”
Section: Discussionmentioning
confidence: 99%